The relationship between quality of academic life and passion for learning among Prince Sattam bin Abdulaziz university students - Al-Desouki, Rasha Bassiouni; Abdellatif, Mohamed Sayed (Research Journal in Advanced Humanities, 2024)
This research aims to identify the level of quality of academic life and Passion for learning among university students and to reveal the relationship between the two variables. A sample of 454 male and female students from Prince Sattam bin Abdulaziz University participated in the study. Utilizing scales for assessing the quality of academic life and passion for learning, researchers employed a descriptive-analytical methodology, particularly the correlational technique, to elucidate the relationship between the variables under investigation. The findings revealed a high level of quality of academic life among the research sample and a high level of Passion for learning (harmonious) with a low level of Passion for learning (obsessive). Furthermore, the research results indicated a statistically significant positive correlation between the four dimensions of quality of academic life (good social relationships, enjoyable academic integration, meaningfulness, effective time management, and overall satisfaction) and harmonious academic passion. On the other hand, a statistically significant negative correlation was found between certain dimensions of quality of academic life (enjoyable academic integration, meaningfulness, effective time management, and overall satisfaction) and obsessive academic passion. However, the relationship between good social relationships and obsessive Passion for learning was not statistically significant. This study highlights the importance of nurturing a harmonious Passion for Learning and addressing obsessive Passion for Learning among university students to enhance academic experiences and overall well-being. Recommendations include targeted interventions within academic institutions, while future research could explore innovative methodologies and comparative studies across diverse cultural and educational settings.